Grit personality trait of doctors and medical students in level 4 acute hospital. Issue 4 (August 2022) - Abd Elwahab, Sami Medani; Cosgrave, John; Doherty, Eva; Lowery, Aoife
Abstract: Introduction: GRIT, defined as passion and perseverance for long-term goals, is a personality trait that is key to academic success and career achievement. Doctors face significant challenges and exposure to stressful situations throughout their career and require high levels of grit and perseverance to achieve success and avoid burn-out. This study aimed to measure overall levels of grit among hospital doctors and medical students and to compare levels of Grit across specialties and career grades. Method: ology: A cross-sectional survey was used to measure GRIT levels using the validated Short Grit Scale (GRIT-S). Hospital doctors and medical students at University Hospital Galway were asked to complete the questionnaire. Gender, age, grade, education, and speciality were recorded. Analysis was conducted using STATA V12.1™ and SPSS 25™. Results: 378 questionnaires were completed with a participation rate of 75.6% eligible for analysis. The female: male ratio was 1.2:1, with a mean age of 29.6 ± 8.3 years. The mean Grit score of participants was 3.56 ± 0.55. Grit trait was independent of gender and increased with age and grade. Consultants had significantly higher mean Grit score (3.86 ± 0.59, p = 0.004). There was no difference between medical specialities, nor between graduate-entry and undergraduate medical students. Conclusion: our results show that medical students and NCHDs alike have high levels of Grit compared to the general population, and the levels increase with career advancement, with the highest scores observed in consultants. This suggests that Grit might be of benefit as an adjunct in the selection process of applicants for training schemes and jobs that require high levels of resilience, as well as an adjunct to monitoring progress in training from a personality and mental health perspective. Highlights: Grit trait appears to change marginally with career grade and speciality, suggesting that a high inherent Grit trait is required to succeed in this profession. Consultants had the highest Grit score compared to NCHD and students. Post-graduate and undergraduate had equivalent Grit scores.